Integrating a Plastic Glucose Biosensor Based on Arrayed Screen-Printed Electrodes Utilizing Magnetic Beads with a Microfluidic Device - Jung-Chuan Chou (IEEE, 2019)
In this study, a novel potentiometric glucose biosensor based on magnetic beads-Nafion-glucose oxidase/graphene oxide/aluminium-doped zinc oxide (MBs-Nafion-GOx/GO/AZO) membranes on a PET substrate with arrayed screen-printed electrodes (SPEs) was proposed. The morphologies, elemental analysis, and surface roughnesses of the sensing membranes were characterized. The sensing parameters of the biosensor were investigated by using the voltage-time (V-T) measurement system, which measured sensitivity, linearity, anti-interference ability, reversibility, temperature effect, and lifetime. A microfluidic device using polydimethylsiloxane (PDMS) was integrated with the V-T measurement system to analyze the response characteristics. The results under static solution and microfluidic flow conditions were compared. The results showed that the average sensitivity and linearity of the biosensor depended on the microfluidic flow rate. The best average sensitivity of the glucose biosensor based on MBs-Nafion-GOx/GO/AZO membranes was 20.35 mV/mM at a flow rate of $15~ μ \text{L}$ /min.